2016
DOI: 10.1177/0160323x16655383
|View full text |Cite
|
Sign up to set email alerts
|

Schoolyard Politics

Abstract: Bullying is a vexing social and policy problem in the United States. Education scholars consistently advocate for comprehensive antibullying policies; however, the forty-nine states that have adopted antibullying programs vary in their embrace of this approach. This article addresses the question of why this is the case. First, it provides a new measure of bullying policy comprehensiveness using item response theory. Second, it examines how social and demographic characteristics, as well as neighbor-state poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Four articles found an atypical pattern of diffusion, where neighbouring policy adoption slowed or decreased the likelihood of local policy adoption, in the policy domains of tobacco control (Pacheco, 2017 ), anti-bullying (Mallinson, 2016 ), abortion liberalization (Boyle et al, 2015 ), and HIV/AIDs (Clark, 2009 ). For example, Clark ( 2009 ) identified that as the proportion of AIDS program adoption in geographically neighbouring countries increased, the time leading to local adoption also increased.…”
Section: Resultsmentioning
confidence: 99%
“…Four articles found an atypical pattern of diffusion, where neighbouring policy adoption slowed or decreased the likelihood of local policy adoption, in the policy domains of tobacco control (Pacheco, 2017 ), anti-bullying (Mallinson, 2016 ), abortion liberalization (Boyle et al, 2015 ), and HIV/AIDs (Clark, 2009 ). For example, Clark ( 2009 ) identified that as the proportion of AIDS program adoption in geographically neighbouring countries increased, the time leading to local adoption also increased.…”
Section: Resultsmentioning
confidence: 99%